2020
DOI: 10.3390/cancers12092707
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Tissue Slice Tandem-Cultures for Quantitative Evaluation of Inhibitory Effects on Invasion and Growth

Abstract: Glioblastomas (GBMs) are the most malignant brain tumors and are essentially incurable even after extensive surgery, radiotherapy, and chemotherapy, mainly because of extensive infiltration of tumor cells into the adjacent normal tissue. Thus, the evaluation of novel drugs in malignant glioma treatment requires sophisticated ex vivo models that approach the authentic interplay between tumor and host environment while avoiding extensive in vivo studies in animals. This paper describes the standardized setup of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Many approaches exist to tackle this complexity, both with their own advantages and disadvantages (reviewed in (Souberan and Tchoghandjian 2020)) and we present the next-level development of OTCs. The concept to study GBM growth using brain slices has been applied in multiple studies (de Bouard et al 2007;Parker et al 2017;Parker et al 2018) mainly employing post-natal brain slices derived from mice, but also from rats grown under high-serum species-unmatched serum-supplementation (Ren et al 2015;Ghoochani et al 2016;Sidorcenco et al 2020), mainly focusing on tumor growth. Some reports show applicability towards analysis on angiogenesis and tumor microenvironment however, these studies mainly rely on further sectioning the slices thereby further increasing the workload.…”
Section: Discussionmentioning
confidence: 99%
“…Many approaches exist to tackle this complexity, both with their own advantages and disadvantages (reviewed in (Souberan and Tchoghandjian 2020)) and we present the next-level development of OTCs. The concept to study GBM growth using brain slices has been applied in multiple studies (de Bouard et al 2007;Parker et al 2017;Parker et al 2018) mainly employing post-natal brain slices derived from mice, but also from rats grown under high-serum species-unmatched serum-supplementation (Ren et al 2015;Ghoochani et al 2016;Sidorcenco et al 2020), mainly focusing on tumor growth. Some reports show applicability towards analysis on angiogenesis and tumor microenvironment however, these studies mainly rely on further sectioning the slices thereby further increasing the workload.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, by harnessing the acquisition speed of LSFM, intrinsic heterogeneity can be accounted for. The concept of studying GBM growth using brain slices has been applied in multiple studies (de Bouard et al, 2007;Parker et al, 2017Parker et al, , 2018 mainly employing post-natal brain slices derived not only from mice but also from rats grown under high-serum, species-unmatched serum supplementation (Ren et al, 2015;Ghoochani et al, 2016;Sidorcenco et al, 2020), mainly focusing on tumor growth. Some reports show applicability toward analysis of angiogenesis and tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Recapitulating all aspects of the brain microenvironment is difficult in vitro . Therefore, ex vivo brain slice assays are used to maintain the complexities of the extracellular matrix and brain architecture and preserve in vivo morphology on which to grow tumour cells or spheroids and monitor cell behaviour in response to treatment ( 208 210 ). It has been shown that GBM stem cell motility decreases compared to 2D culture when maintained in this way, presumably due to additional barriers such as the extracellular matrix and the need for extracellular matrix remodelling ( 211 ).…”
Section: Outlook and Conclusionmentioning
confidence: 99%